Advanced Control Solution for Three-Phase Induction Motors in Magnetic Saturation Region: Published online: 22/10/2025 - Nguyen, Vinh Quan; Nguyen, Nhan Bon; Le, Thanh Lam; Nguyen, Minh Tam; Bui, Thuc Minh (Journal of Technical Education Science, 2025)
In many industrial applications, induction motors are often required to operate in the magnetic saturation region to meet demands for high load or torque. However, in this region, the characteristics of the motor become nonlinear, rendering traditional control methods based on linear assumptions ineffective. This research focuses on the modeling and control of induction motors under magnetic saturation conditions. The motor model is developed in the d-q reference frame, incorporating nonlinear characteristics of both the stator and rotor. The study also introduces a signal modulation technique for a three-level inverter to enhance voltage conversion efficiency. To address the challenges posed by saturation effects and random disturbances, an enhanced direct torque control (EDTC) algorithm is proposed. This algorithm aims to mitigate the influence of magnetic saturation while maintaining robust performance. The proposed solution is validated through experimental testing conducted on the OPAL-RT system. Results confirm that the EDTC approach ensures the stator flux and speed closely track their reference values, even in the presence of noise. The control system delivers high performance, maintaining total harmonic distortion (THD) of the current within the range of 11% to 16%, underscoring its practicality and efficiency.